Physical And Chemical Characterization Of Complex Gold Ore From Peranggih Deposit - Hamizai @ Hamizzi, Mohamad Faiz (Universiti Sains Malaysia, 2018)
In this study, the gold ore was obtained from Peranggih deposit, Pahang by the permission of Selinsing Gold Mine Manager. A pre-concentration process was conducted using Mozley table in order to observe whether the gold can be separated by gravity due to its heavy density and to eliminate any impurities. A characterization study was done on bulk, size fractions and pre-concentrate samples in order to identify the minerals composition via XRD, XRF, SEM/EDX analysis and optical microscope study. The concentrate and tailing from gravity separation was sent to XRF and SEM to observe the mineral composition and grain. From the XRF and SEM/EDX analysis, a few significant elements were found in the sample, with the highest is quartz, followed by aluminium, potassium, iron and others. This result was also supported by SEM/EDX. As for assaying method, two methods were conducted in order to determine the gold content in the sample, which is fire assay analysis and bottle roll test. Both of this method need AAS to determine the concentration of gold inside the pregnant solution obtained. The fire assay should be able to determine the overall amount of gold inside the sample while bottle roll test only able to leach out the free mill gold. The head grade obtained is 0.036 g/t and the free milling gold obtained is 0.531 g/t.